2015
DOI: 10.1371/journal.pone.0125958
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Residents’ Communication Learning Process in the Workplace: A Five-Phase Model

Abstract: ContextCompetency-based education is a resurgent paradigm in professional medical education. However, more specific knowledge is needed about the learning process of such competencies, since they consist of complex skills. We chose to focus on the competency of skilled communication and want to further explore its learning process, since it is regarded as a main competency in medical education.ObjectiveThis study aims to explore in more detail the learning process that residents in general practice go through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 45 publications
(36 reference statements)
1
48
0
2
Order By: Relevance
“…They are learned by doing, by experiencing, by getting feedback, by new experimentation, etc. In recent studies on communication [ 11 , 12 ], residents learned communication by first using ‘learned’ and somewhat artificial techniques in actual practice, then with ample feedback on authentic clinical actions (video assessment, peer feedback, supervisor interactions); under safe conditions, communication behaviours become personalized and internalized. Finally, communication behaviours become part of the personal clinical repertoire and can be used flexibly, all depending on the context and the purpose of the encounter.…”
Section: Embracing Competencies For Learning Has Formidable Educationmentioning
confidence: 99%
“…They are learned by doing, by experiencing, by getting feedback, by new experimentation, etc. In recent studies on communication [ 11 , 12 ], residents learned communication by first using ‘learned’ and somewhat artificial techniques in actual practice, then with ample feedback on authentic clinical actions (video assessment, peer feedback, supervisor interactions); under safe conditions, communication behaviours become personalized and internalized. Finally, communication behaviours become part of the personal clinical repertoire and can be used flexibly, all depending on the context and the purpose of the encounter.…”
Section: Embracing Competencies For Learning Has Formidable Educationmentioning
confidence: 99%
“…It was striking that the doctors all said they were satisfied with their conversation, while the observers concluded that doctors did not practice the relevant ICC skills. An explanation could be that the doctors need to be confronted with their communication behaviour before they can improve their communication skills [ 15 ]. Finally, we need to say that the complexity of ICC cannot be grasped in a list of do’s and don’ts.…”
Section: Discussionmentioning
confidence: 99%
“…While the theoretical knowledge on ICC skills and the necessity of using these skills have been established [ 6 , 8 , 13 ], several researchers argue that the scientific field of ICC between doctors and patients in real practice is still too small to develop focused training in ICC [ 7 , 14 ] and that just giving feedback does not cover the full picture of skilled medical communication [ 15 ]. It is, for example, unknown which ICC skills are already used by doctors and how they are used.…”
Section: Introductionmentioning
confidence: 99%
“…Een recente studie vergeleek een vervolgopleiding waarin veel aandacht wordt besteed aan communicatie (huisartsopleiding) met een opleiding waar minder aandacht aan communicatie wordt besteed (chirurgie) [37]. Interessant is dat door deze communicatieaandacht communicatievaardigheden internaliseren en personaliseren [38]. Dat gebeurt door een proces van confrontatie (o. a. door feedback), reflectie, veilige oefening, nieuwe feedback en rolmodellen.…”
Section: Conclusieunclassified